Preparation method of lithium ion battery silicon-based negative electrode binder

By using small molecular polymers with low glass transition temperature and precipitation polymerization methods in the silicon-based anode materials of lithium-ion batteries, the problem of silicon-based anode materials falling off due to volume expansion during charging and discharging is solved, and higher electrochemical performance and electrode stability are achieved.

CN119684939APending Publication Date: 2025-03-25YANTAI YI BIN NEW MSTAR TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411866533.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing silicon-based anode material of lithium-ion batteries falls off due to volume expansion during charging and discharging, and the adhesive cannot effectively adapt to huge volume changes, resulting in electrical isolation and unstable SEI formation.

Method used

A method for preparing a silicon-based negative electrode binder for lithium ion batteries is adopted, including preparing a small molecular polymer with a low glass transition temperature, preparing the adhesive liquid by precipitation polymerization, and introducing a small molecular polymer with a low glass transition temperature in the preparation, finally washing it with water and adding lithium salt to neutralize it, obtaining a silicon-based negative electrode binder for lithium ion batteries.

Benefits of technology

This method provides more active sites by forming an intercrosslinked network structure, effectively inhibiting the volume expansion of the silicon negative electrode, improving electrochemical performance, and firmly interacting with the silicon particles through the abundant polar groups, thereby improving the mechanism stability of the electrode.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery materials, and discloses a lithium ion battery silicon-based negative electrode binder preparation method, which comprises: 1) preparing a small molecule polymer with a low glass transition temperature; (2) preparing adhesive liquid in a precipitation polymerization mode, adding an initiator for multiple times in the preparation process, and adding the small-molecule polymer with the low glass transition temperature in the step (1) when the mass of the added initiator reaches 65% of the total mass of the initiator; (3) washing the obtained adhesive liquid with water, and adding lithium salt for neutralization to obtain the silicon-based negative electrode adhesive for the lithium ion battery; volume expansion of the silicon negative electrode in the charge-discharge cycle process is effectively inhibited, and the electrochemical performance of the lithium ion battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium electronic battery materials, and in particular to a method for preparing a silicon-based negative electrode binder for lithium ion batteries. Background Art

[0002] Currently, most commercial lithium-ion batteries use graphite as the negative electrode. In order to obtain lithium-ion batteries with higher energy density, silicon is considered to be the most ideal new generation negative electrode material, with a theoretical capacity of up to 4200mAh / g, far exceeding the current unit capacity of graphite of 372mAh / g. Unlike graphite materials, the high specific capacity of silicon stems from the alloying process of silicon and lithium, so silicon negative electrode materials will not be co-embedded with the electrolyte solvent, and thus have a wider range of adaptability to electrolytes. Compared with carbon materials, silicon has a higher lithium deintercalation potential, which can effectively avoid lithium precipitation during high-rate charge and discharge, and can improve battery safety.

[0003] However, silicon does not have a layered structure like graphite. Its lithium storage mechanism is the same as other metals, which is carried out through alloying and dealloying with lithium ions. Its charge and discharge electrode reaction is as follows: Si+xLi++xe-→LiXSi. During the discharge process, as the voltage drops, a core-shell structure is formed in which lithium-embedded silicon and non-lithium-embedded crystalline silicon coexist. As the depth of lithium embedding increases, lithium ions react with internal crystalline silicon to form lithium-silicon alloys, which eventually exist in the form of an alloy of Li15 Si4. During this process, the silicon-based negative electrode material will undergo a huge (about 300%) volume change. Although the silicon negative electrode has excellent energy storage, its huge volume change before and after charging and discharging seriously hinders its commercialization.

[0004] The main function of the binder is to fix the silicon anode on the current collector to prevent the silicon anode from falling off due to volume expansion during the charge and discharge process. Polyacrylic acid (PAA) binders themselves have more functional groups, which can form a good interaction force with silicon particles, effectively fix silicon particles on the current collector, and provide good electron and ion transmission channels. However, PAA itself has a high glass transition temperature and is very brittle, which limits its application in silicon anodes. At present, the adhesion of PAA to silicon anodes can be improved by grafting or network cross-linking. However, the mechanical properties of grafted PAA are insufficient and cannot effectively alleviate the pulverization of silicon nanoparticles; and the bonding between network cross-linked PAA and silicon is insufficient, which cannot effectively adapt to the volume expansion of silicon. In addition, biomass polymer binders have also received great attention due to their biodegradability and natural abundance, such as sodium alginate (SA) and carboxymethyl cellulose (CMC). Compared with synthetic polymer binders, biomass materials with abundant polar groups (hydroxyl, carboxyl, amino) are more likely to form strong interactions with the Si-OH of the SiO2 layer on silicon particles, improving the structural stability of the electrode. However, the above polymers are not sufficient to accommodate huge volume changes due to their linear or branched structures, resulting in electrical isolation of silicon and the resulting unstable SEI formation.

[0005] Therefore, it is very necessary to develop a silicon negative electrode binder that has strong bonding strength to the silicon negative electrode, low glass transition temperature, can effectively adapt to the volume expansion of silicon, and does not affect the transfer of electrons and ions. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a silicon-based negative electrode binder for a lithium ion battery.

[0007] Terminology Note:

[0008] A method for preparing a silicon-based negative electrode binder for a lithium-ion battery comprises the following steps:

[0009] 1) Prepare small molecule polymers with low glass transition temperature;

[0010] 2) Preparing the adhesive liquid by precipitation polymerization, adding the initiator in multiple times during the preparation, and when the mass of the added initiator reaches 65% of the total mass of the initiator, adding the small molecule polymer with a low glass transition temperature in step 1);

[0011] 3) The obtained adhesive liquid is washed with water, and lithium salt is added for neutralization to obtain a silicon-based negative electrode binder for lithium-ion batteries.

[0012] As a preferred technical solution, the small molecule polymer with a low glass transition temperature in 1) is reactivated and an emulsion polymerization method is adopted to obtain the small molecule polymer with a low glass transition temperature.

[0013] As a preferred technical solution, the emulsion polymerization method is:

[0014] 300-500 parts by weight of deionized water, 5 parts by weight of initiator, 3 parts by weight of n-dodecyl mercaptan molecular weight regulator are added into a pre-emulsification kettle, 15-25 parts by weight of SR-10 reactive emulsifier is added into the pre-emulsification kettle, 1600-1900 parts by weight of monomer isooctyl acrylate, 100-150 parts by weight of acrylic acid, 180-220 parts by weight of methyl methacrylate are added, and the mixture is stirred sufficiently to prevent oil and water from separating, and a pre-emulsion is prepared by the above steps; 1400-1600 parts by weight of water and 4-6 parts by weight of SR-10 reactive emulsifier are added into a reaction kettle, the temperature is raised to 85° C., the pre-emulsion is directly added dropwise without adding seeds, the pre-emulsion is added dropwise within 4-6 hours, and the temperature is controlled at 85±1° C., and a cross-linking monomer No. 1 with a low glass transition temperature, i.e., a small molecule polymer with a low glass transition temperature is obtained.

[0015] As a preferred technical solution, 400 parts by weight of deionized water, 5 parts by weight of ammonium persulfate, 3 parts by weight of n-dodecyl mercaptan molecular weight regulator, 1870 parts by weight of monomer isooctyl acrylate, 123 parts by weight of acrylic acid, and 200 parts by weight of methyl methacrylate are added to the pre-emulsification kettle, and the mixture is stirred sufficiently to prevent oil and water from separating. 400 parts by weight of water and 5 parts by weight of SR-10 emulsifier are added to the reactor, the temperature is raised to 85°C, and the pre-emulsion is directly added without adding seeds. The pre-emulsion is added dropwise within 5 hours, during which the temperature is controlled at 85±1°C to obtain a cross-linking monomer No. 1 with a glass transition temperature of -55°C.

[0016] As a preferred technical solution, the precipitation polymerization method in 2) is:

[0017] Add 3500-3700 parts by weight of water, 300-350 parts by weight of acrylic acid, 50-60 parts by weight of hydroxymethyl acrylamide, and 450-460 parts by weight of crosslinking monomer No. 2 to the reactor, raise the temperature to 75°C, add 15% of the total amount of initiator, control the temperature to react for 1 hour, slowly drop 50% of the total mass of the initiator within 2.5 hours, then add 550-650 parts by weight of a small molecule polymer with a low glass transition temperature, raise the temperature to 80°C, continue to drop the remaining initiator within 1.5 hours, keep the temperature for 1 hour after the reaction is completed to reduce the residual monomer, cool to below 50°C, precipitate for 10 minutes, and extract the supernatant.

[0018] As a preferred technical solution, 3620 parts by weight of water, 320 parts by weight of acrylic acid, 57 parts by weight of hydroxymethyl acrylamide, and 457 parts by weight of acrylonitrile are added to the reactor, the temperature is raised to 75°C, 15% of the total amount of ammonium persulfate is added, and the temperature is controlled to react for 1 hour, and then 50% of the total amount of ammonium persulfate is slowly added dropwise within 2.5 hours, and then 600 parts by weight of cross-linking monomer No. 1 is added, the temperature is raised to 80°C, and the remaining initiator is continued to be added dropwise within 1.5 hours. After the reaction is completed, the temperature is kept for 1 hour to reduce the residual monomers, the temperature is lowered to below 50°C, and after precipitation for 10 minutes, the supernatant is extracted.

[0019] As a preferred technical solution, in the above 3), appropriate deionized water is added to the supernatant of step 2), stirring is started, 440 parts by weight of lithium hydroxide aqueous solution is slowly added, the pH is adjusted to 7-9, and after the solid is dissolved, the solid content is adjusted to 20% to obtain a finished product with a glass transition temperature of 22.5°C.

[0020] As a preferred technical solution, the lithium hydroxide aqueous solution includes 40 parts by weight of lithium hydroxide and 400 parts by weight of water.

[0021] The initiator is ammonium persulfate.

[0022] A method for preparing a silicon-based negative electrode binder for lithium-ion batteries is adopted, which includes the following steps: 1) preparing a small molecule polymer with a low glass transition temperature; 2) preparing a binder liquid by precipitation polymerization, wherein an initiator is added in multiple times during the preparation, and when the mass of the added initiator reaches 65% of the total mass of the initiator, the small molecule polymer with a low glass transition temperature in step 1) is added; 3) washing the obtained binder liquid with water, adding lithium salt for neutralization, and obtaining a silicon-based negative electrode binder for lithium-ion batteries.

[0023] Advantages of the present invention:

[0024] 1. The present invention forms a cross-linked network structure by reacting different monomers in different polymerization modes, providing more active sites for the silicon negative electrode and the binder, solving the problem that the existing linear polymer as the negative electrode binder cannot interact well with the silicon particles, effectively inhibiting the volume expansion of the silicon negative electrode during the charge and discharge cycle, and further improving the electrochemical performance of the lithium-ion battery.

[0025] 2. The silicon-based negative electrode binder for lithium-ion batteries of the present invention has a material with more abundant polar groups (hydroxyl and carboxyl groups), which is more likely to form a strong interaction force with the Si-OH of the SiO2 layer on the silicon particles, thereby improving the structural stability of the electrode.

[0026] 3. The binder of the present invention mainly uses the groups obtained by chemical reaction of the first extremely low glass transition temperature compound and the second structural compound as network nodes to obtain a polymer with a relatively low glass transition temperature network structure. During the cycle, it can not only buffer the volume expansion, but also form hydrogen bonds with the active material to obtain a long-cycle silicon negative electrode material. The lithium hydroxide used as a neutralizer greatly improves the effect of the binder on the ions in the lithium-ion battery.

[0027] 4. The molecular weight of the multi-polymer is extremely large and the viscosity is very high. It can also ensure that the cohesive force is large enough to bond the silicon-based negative electrode material and the conductive agent together well, avoiding the powdering of the negative electrode paste when the silicon expands, ensuring the smooth flow of all active material electrons and lithium ion channels inside the negative electrode paste, and exerting the performance of all active materials.

[0028] 5. Using soap-free emulsion polymerization, adding polymers with appropriate molecular weight halfway through the reaction changes the film-forming and cross-linking methods of the final adhesive, and obtaining a polymer with a relatively low glass transition temperature network structure, thus solving various problems of PAA-type bonding linear structures. DETAILED DESCRIPTION

[0029] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0030] Embodiment 1:

[0031] 1) Add 300 parts by weight of deionized water, 5 parts by weight of ammonium persulfate, 3 parts by weight of n-dodecyl mercaptan molecular weight regulator into a pre-emulsification kettle, add 15 parts by weight of SR-10 reactive emulsifier into the pre-emulsification kettle, add 1600 parts by weight of monomer isooctyl acrylate, 100 parts by weight of acrylic acid, and 180 parts by weight of methyl methacrylate, stir well to prevent oil and water from separating, and prepare a pre-emulsion liquid by the above steps; add 1400 parts by weight of water and 4 parts by weight of SR-10 reactive emulsifier into the reaction kettle, heat it to 85° C., directly add the pre-emulsion liquid without adding seeds, and complete the addition of the pre-emulsion liquid within 4 hours, during which the temperature is controlled at 85±1° C., and obtain a cross-linking monomer No. 1 with a low glass transition temperature, that is, a small molecule polymer with a low glass transition temperature.

[0032] 2) Adopting precipitation polymerization to prepare adhesive liquid, the precipitation polymerization method is:

[0033] Add 3500 parts by weight of water and 300 parts by weight of acrylic acid, 50 parts by weight of hydroxymethyl acrylamide, and 450 parts by weight of acrylonitrile to the reactor, heat it to 75°C, add 15% of the total amount of ammonium persulfate, control the temperature and react for 1 hour, slowly drop 50% of the total mass of ammonium persulfate within 2.5 hours, then add 550 parts by weight of a small molecule polymer with a low glass transition temperature, heat it to 80°C, continue to drop the remaining initiator within 1.5 hours, keep the temperature for 1 hour after the reaction to reduce the residual monomer, cool it to below 50°C, precipitate for 10 minutes, and extract the supernatant. 15 parts by weight of ammonium persulfate are used in the above 2).

[0034] 3) Add appropriate amount of deionized water to the supernatant of step 2) and start stirring, slowly add 440 parts by weight of lithium hydroxide aqueous solution, adjust the pH to 7-9, adjust the solid content to 20% after the solid is dissolved, and obtain a finished product with a glass transition temperature of 22.5°C.

[0035] The lithium hydroxide aqueous solution includes 40 parts by weight of lithium hydroxide and 400 parts by weight of water.

[0036] Embodiment 2:

[0037] 1) Add 500 parts by weight of deionized water, 5 parts by weight of ammonium persulfate, and 3 parts by weight of n-dodecyl mercaptan molecular weight regulator into a pre-emulsification kettle, add 25 parts by weight of SR-10 reactive emulsifier into the pre-emulsification kettle, add 1900 parts by weight of monomer isooctyl acrylate, 150 parts by weight of acrylic acid, and 220 parts by weight of methyl methacrylate, and stir well to prevent oil and water from separating. The above steps prepare a pre-emulsion; add 1600 parts by weight of water and 6 parts by weight of SR-10 reactive emulsifier into the reaction kettle, heat it to 85° C., and directly drop the pre-emulsion without adding seeds. The pre-emulsion is added dropwise within 6 hours, and the temperature is controlled at 85±1° C. to obtain a cross-linking monomer No. 1 with a low glass transition temperature, that is, a small molecule polymer with a low glass transition temperature.

[0038] 2) Adopting precipitation polymerization to prepare adhesive liquid, the precipitation polymerization method is:

[0039] Add 3700 parts by weight of water and 350 parts by weight of acrylic acid, 60 parts by weight of hydroxymethyl acrylamide, and 460 parts by weight of acrylonitrile to the reactor, heat it to 75°C, add 15% of the total amount of ammonium persulfate, control the temperature and react for 1 hour, slowly drop 50% of the total mass of ammonium persulfate within 2.5 hours, then add 650 parts by weight of a small molecule polymer with a low glass transition temperature, heat it to 80°C, continue to drop the remaining initiator within 1.5 hours, keep the temperature for 1 hour after the reaction to reduce the residual monomer, cool it to below 50°C, precipitate for 10 minutes, and extract the supernatant. 15 parts by weight of ammonium persulfate are used in the above 2).

[0040] 3) Add appropriate amount of deionized water to the supernatant of step 2) and start stirring, slowly add 440 parts by weight of lithium hydroxide aqueous solution, adjust the pH to 7-9, adjust the solid content to 20% after the solid is dissolved, and obtain a finished product with a glass transition temperature of 22.5°C.

[0041] The lithium hydroxide aqueous solution includes 40 parts by weight of lithium hydroxide and 400 parts by weight of water.

[0042] Embodiment 3:

[0043] 1) Add 400 kg of deionized water, 5 kg of ammonium persulfate, and 3 kg of n-dodecyl mercaptan molecular weight regulator into a pre-emulsification kettle, add 20 kg of SR-10 emulsion into the pre-emulsification kettle, add 1870 kg of monomer isooctyl acrylate, 123 kg of acrylic acid, and 200 kg of methyl methacrylate, and stir well to prevent oil and water from separating. The above steps prepare a pre-emulsion; add 1500 kg of water and 5 kg of SR-10 emulsifier into a reaction kettle, heat to 85° C., and directly drop the pre-emulsion without adding seeds. The pre-emulsion is added dropwise within 6 hours, during which the temperature is controlled at 85±1° C., to obtain a cross-linking monomer No. 1 with a particle size of 40 to 60 nm, a solid content of 53.6%, and a glass transition temperature of -55° C., that is, a small molecule polymer with a low glass transition temperature.

[0044] 2) Adopting precipitation polymerization to prepare adhesive liquid, the precipitation polymerization method is:

[0045] Add 3620kg of water and 320kg of acrylic acid, 57kg of hydroxymethyl acrylamide, and 457kg of acrylonitrile to the reactor, heat it to 75°C, add 15% of the total amount of ammonium persulfate, control the temperature and react for 1h, slowly drop 50% of the total mass of ammonium persulfate within 2.5 hours, then add 600kg of cross-linking monomer No. 1, heat it to 80°C, continue to drop the remaining initiator within 1.5h, keep the temperature for 1h after the reaction to reduce the residual monomer, cool it to below 50°C, precipitate for 10 minutes, and extract the supernatant. 15kg of ammonium persulfate is used in the above 2).

[0046] 3) Add appropriate amount of deionized water to the supernatant of step 2) and start stirring, slowly flow in lithium hydroxide aqueous solution, adjust the pH to 7-9, adjust the solid content to 20% after the solid is dissolved, and obtain a finished product with a glass transition temperature of 22.5°C.

[0047] The lithium hydroxide aqueous solution includes 40 kg of lithium hydroxide and 400 kg of water.

[0048] The solid content of the finished product is 20.6%, the viscosity is 5W-8W (25°C) and the glass transition temperature is 22.5°C.

[0049] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a silicon-based negative electrode binder for a lithium-ion battery, characterized in that: The following steps are involved: 1) Prepare small molecule polymers with low glass transition temperature; 2) Preparing the adhesive liquid by precipitation polymerization, adding the initiator in multiple times during the preparation, and when the mass of the added initiator reaches 65% of the total mass of the initiator, adding the small molecule polymer with a low glass transition temperature in step 1); 3) The obtained adhesive liquid is washed with water, and lithium salt is added for neutralization to obtain a silicon-based negative electrode binder for lithium-ion batteries.

2. A method for preparing a silicon-based negative electrode binder for lithium-ion batteries according to claim 1, characterized in that: The small molecule polymer with a low glass transition temperature in 1) is activated again, and an emulsion polymerization method is adopted to obtain a small molecule polymer with a low glass transition temperature.

3. A method for preparing a silicon-based negative electrode binder for lithium-ion batteries according to claim 2, characterized in that: The emulsion polymerization method is: 300-500 parts by weight of deionized water, 5 parts by weight of initiator, 3 parts by weight of n-dodecyl mercaptan molecular weight regulator are added into a pre-emulsification kettle, 15-25 parts by weight of SR-10 reactive emulsifier is added into the pre-emulsification kettle, 1600-1900 parts by weight of monomer isooctyl acrylate, 100-150 parts by weight of acrylic acid, 180-220 parts by weight of methyl methacrylate are added, and the mixture is stirred sufficiently to prevent oil and water from separating, and a pre-emulsion is prepared by the above steps; 1400-1600 parts by weight of water and 4-6 parts by weight of SR-10 reactive emulsifier are added into a reaction kettle, the temperature is raised to 85° C., the pre-emulsion is directly added dropwise without adding seeds, the pre-emulsion is added dropwise within 4-6 hours, and the temperature is controlled at 85±1° C., and a cross-linking monomer No. 1 with a low glass transition temperature, i.e., a small molecule polymer with a low glass transition temperature is obtained.

4. A method for preparing a silicon-based negative electrode binder for lithium-ion batteries according to claim 3, characterized in that: In the pre-emulsification kettle, 400 parts by weight of deionized water, 5 parts by weight of ammonium persulfate, 3 parts by weight of n-dodecyl mercaptan molecular weight regulator, 1870 parts by weight of monomer isooctyl acrylate, 123 parts by weight of acrylic acid, and 200 parts by weight of methyl methacrylate were added, and the mixture was stirred sufficiently to prevent oil and water from separating. 400 parts by weight of water and 5 parts by weight of SR-10 emulsifier were added to the reaction kettle, and the temperature was raised to 85°C. The pre-emulsion was directly added dropwise without adding seeds. The pre-emulsion was added dropwise within 5 hours, during which the temperature was controlled at 85±1°C to obtain a cross-linking monomer No. 1 with a glass transition temperature of -55°C.

5. The method for preparing a silicon-based negative electrode binder for lithium-ion batteries according to claim 1, characterized in that: The precipitation polymerization method in 2) is: Add 3500-3700 parts by weight of water, 300-350 parts by weight of acrylic acid, 50-60 parts by weight of hydroxymethyl acrylamide, and 450-460 parts by weight of crosslinking monomer No. 2 to the reactor, raise the temperature to 75°C, add 15% of the total amount of initiator, control the temperature to react for 1 hour, slowly drop 50% of the total mass of the initiator within 2.5 hours, then add 550-650 parts by weight of a small molecule polymer with a low glass transition temperature, raise the temperature to 80°C, continue to drop the remaining initiator within 1.5 hours, keep the temperature for 1 hour after the reaction is completed to reduce the residual monomer, cool to below 50°C, precipitate for 10 minutes, and extract the supernatant.

6. A method for preparing a silicon-based negative electrode binder for lithium-ion batteries according to claim 5, characterized in that: Add 3620 parts by weight of water, 320 parts by weight of acrylic acid, 57 parts by weight of hydroxymethyl acrylamide, and 457 parts by weight of acrylonitrile to the reactor, raise the temperature to 75°C, add 15% of the total amount of ammonium persulfate, control the temperature and react for 1 hour, slowly add 50% of the total amount of ammonium persulfate within 2.5 hours, then add 600 parts by weight of cross-linking monomer No. 1, raise the temperature to 80°C, continue to add the remaining initiator within 1.5 hours, keep the temperature for 1 hour after the reaction to reduce the residual monomer, cool to below 50°C, precipitate for 10 minutes, and extract the supernatant.

7. The method for preparing a silicon-based negative electrode binder for lithium-ion batteries according to claim 1, characterized in that: In the above 3), appropriate amount of deionized water is added to the supernatant of step 2), stirring is started, 440 parts by weight of lithium hydroxide aqueous solution is slowly added, the pH is adjusted to 7-9, and after the solid is dissolved, the solid content is adjusted to 20%, to obtain a finished product with a glass transition temperature of 22.5°C.

8. A method for preparing a silicon-based negative electrode binder for lithium-ion batteries according to claim 7, characterized in that: The lithium hydroxide aqueous solution includes 40 parts by weight of lithium hydroxide and 400 parts by weight of water.